FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA UNTUK BERINVESTASI DI REKSADANA (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Unisma) - Tasya Anggita Veronika; Abdul Wahid Mahsuni; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the factors that influence student interest in investing in mutual funds in students of the Faculty of Economics and Business, Islamic University of Malang.  factors used are (1) knowledge, (2) benefits, and (3) perceived convenience. To determine the sample in this study using the Slovin formula. And the results show that the sample used in this study was 100 students. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. Testing the data used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that (1) the independent variable simultaneously had a significant effect on the dependent variable. Based on the partial test results, (2) the knowledge and benefits variables affect student interest, (3) while the perceived convenience variable has no effect on student interest.Keywords: Mutual Funds, Knowledge, Benefits, Perception of Ease and Interest in Investing.